Hubungan Dukungan Sosial Teman Sebaya dengan Self-Disclosure pada Siswa SMA di Lingkungan Pesantren - Adelia Rafif Talaby Susilo; Nur Azmi Wiantina; Feny Nida Fitriyani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to examine the relationship between peer social support and self-disclosure among senior high school students in a pesantren (Islamic boarding school) setting in the Jabodetabek area. This research employed a quantitative correlational design with a sample of 208 students selected through purposive sampling. Data were collected using the Peer Social Support Scale developed based on Sarafino and Smith's (2014) theory, encompassing four dimensions (emotional, instrumental, informational, and appraisal support), and the Self-Disclosure Scale adapted from the Revised Self-Disclosure Scale (RSDS) by Wheeless (1976), measuring five dimensions (intent, amount, valence, depth/intimacy, and honesty/accuracy). Instrument validity was assessed through expert judgment and construct validity using Confirmatory Factor Analysis (CFA), while reliability was measured using Cronbach's Alpha (α = 0.950). Prior to correlation analysis, a normality test using the One-Sample Kolmogorov-Smirnov test revealed that the data were not normally distributed (p = 0.000 < 0.05); therefore, data were analyzed using Spearman's rank correlation. The results showed a significant positive relationship between peer social support and self-disclosure (r = 0.595; p = 0.000), indicating a moderate-to-strong relationship. These findings suggest that higher perceived peer social support corresponds to higher levels of self-disclosure among pesantren students. The findings have practical implications for Islamic Guidance and Counseling (BKPI) services, particularly in designing peer-based intervention programs to enhance students' self-disclosure and mental health in pesantren settings.